A CLINICAL STUDY ON THE EFFECT OF BOERHAAVIA DIFFUSA (PUNARNAVA) IN ESSENTIAL HYPERTENSION (AYUSHDHARA, 2016)
Essential Hypertension (EHTN) has already emerged as a non-communicable pandemic with considerable public health challenges. Its prevalence in India ranges from 20-40% in urban adults and 12-17% among rural adults which is rapidly increasing. The present clinical study was an approach to evaluate the efficacy of Punarnava (Boerhaavia diffusa) (BD) capsules in mild EHTN. 60 patients were randomly selected and divided into two groups. Their blood pressure (BP) measurement, serum urea & creatinine, total cholesterol, serum Na+ & K+, ECG & X-ray Chest (PA view) were done before and at the end of the treatment. Group T was given the trial drug (each capsule containing 250 mg of BD extract) in a dose of 2 capsules twice daily with water for six weeks. Group C was given the control drug (each tablet containing 12.5 mg of Hydrochlorothiazide (HCTZ) in a dose of 1 tablet once daily in the morning with water for six weeks. BD was found effective in reducing both systolic & diastolic blood pressure with statistical significance & also significantly improved the subjective complains in EHTN. Moreover it was well tolerated by most of the subjects and did not produce any harmful side effects.